1977
DOI: 10.1210/endo-101-2-365
|View full text |Cite
|
Sign up to set email alerts
|

Heterotransplantation of Human Fetal Pituitaries in Nude Mice*

Abstract: The heterotransplantation of minced human fetal pituitaries into adult thymus-aplastic nude mice is described. Development and growth of such grafts were observed in 16 of 21 recipient mice. Histological examinations of the transplants showed typical adenohypophyseal cells. Neurohypophyseal cells could never be detected. The levels of human growth hormone (hGH) varied between 0.8 and 42.0 ng/ml in the plasma of the hosts (mean value 7.2 ng/ml, by radioimmunoassay).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

1979
1979
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
3
6
0
1
Order By: Relevance
“…However, on histo logical examination the remaining tumor ap peared to be viable. Moreover, mean hGH levels in 15 nude mice with fetal human pitu itary grafts exhibiting growth, was 7.2 ng/ml [5] , which is in the same range we and others [6] found with adenoma grafts. In contrast with the benign human pituitary' adenomas, a malignant serially transplanted rat pituitary tumor-secreting PRL.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, on histo logical examination the remaining tumor ap peared to be viable. Moreover, mean hGH levels in 15 nude mice with fetal human pitu itary grafts exhibiting growth, was 7.2 ng/ml [5] , which is in the same range we and others [6] found with adenoma grafts. In contrast with the benign human pituitary' adenomas, a malignant serially transplanted rat pituitary tumor-secreting PRL.…”
Section: Discussionsupporting
confidence: 80%
“…HPRL and hGH were detectable only in mice bearing tumors from hyperpro lactinemic and/or acromegalic patients, which was also shown by others [6]. Further more, hGH has been found in nude mice after heterotransplantation of normal fetal pituitary tissue [5]. Il cannot be excluded that hormone levels in the recipient mice repre sented hormone released from dying cells as suggested by the decrease in size of the trans planted adenoma tissue.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We used the HLM model to try and compare the release of cell surface components from xenografted human foetal kidney tissue with components released by the GYL tumour. However, in common with other reports of human foetal tissue xenografted into nude mice, we found that the foetal kidney tissue would not maintain over a long period (Povlsen et al, 1974;Bastert et al, 1977;Usadel et al, 1977). Careful scrutiny of the histological sections of the foetal kidney xenografts showed only a very few mitotic figures compared to the kidney tumour xenografts.…”
Section: Xenograftssupporting
confidence: 85%
“…It is possible to follow the histogenesis of human embryonic organs by grafting the tissues of ther apeutic abortuses Skakkcbaek et al. 1974;Bastert et al. 1977;Bowker and Turmer.…”
Section: Discussionmentioning
confidence: 99%